Analysis of the Role of Social Media in Shaping Public Trust in Minahasa Regency Government Policies - Vleike Tarore, Steven; Mantiri, Jeane; Hardiyanti, Hardiyanti (Indonesian Association for Public Administration (IAPA), 2025)
Public trust is widely recognized as a cornerstone of democratic governance and effective public administration. In recent years, however, public trust in government institutions has faced significant challenges due to political controversies, policy failures, and the proliferation of misinformation in digital spaces. Social media has emerged as a critical arena where governments communicate policies, citizens respond, and public perceptions are shaped. This study explores the role of social media in shaping public trust in local government policies, focusing on Minahasa Regency, Indonesia. Using a qualitative research design, the study employs document analysis, content analysis of official government social media accounts, and secondary literature review to assess the dynamics of trust-building in digital governance. Findings suggest that social media functions as both a facilitator and a potential threat to public trust. On the positive side, social media enhances transparency, accelerates information dissemination, fosters two-way communication, and enables citizens’ active participation in policy discourse. These dynamics contribute to performance-based trust and strengthen social capital, consistent with theoretical frameworks by Mishler and Rose (2001) and Putnam (2000). Conversely, challenges such as inconsistent government responses, limited digital literacy, and exposure to misinformation undermine trust and exacerbate public skepticism. The study contributes to scholarly debates on digital governance by demonstrating how social media operates as a participatory democratic tool at the local level in Indonesia. Practical implications highlight the need for governments to institutionalize social media as a governance instrument, ensure consistency and creativity in content delivery, strengthen digital literacy among citizens, and collaborate strategically with community influencers to broaden legitimacy. By situating Minahasa within global debates on governance and communication, this study underscores the dual role of social media as both a vehicle of trust and a source of contestation in contemporary public policy.